Prevalence and quantitative analysis of indium-111 pentetreotide (Octreoscan) uptake in the pancreatic head on SPECT/CT imaging: establishing a region of interest-based pathological uptake threshold. Issue 7 (July 2019) - Derakhshan, Jamal J.; Farwell, Michael D.
Abstract : Objective: Determine the prevalence of benign indium-111 ( 111 In) pentetreotide uptake in the pancreatic head and determine if a semi-quantitative method can be used to differentiate physiologic from pathologic uptake. Patients and methods: Institutional Review Board-approved, HIPAA-compliant retrospective review of 197 somatostatin receptor scintigraphy studies performed in 136 patients, from December 2012 to November 2013 at a large academic medical center. The pancreatic head uptake was visually graded and for all positive cases, two-dimensional and three-dimensional ratios of the pancreatic head to normal liver uptake were calculated. Statistical analysis using paired and two-sample t -tests was performed. Results: Nineteen of one hundred twenty-nine (14.7%) patients had benign 111 In pentetreotide uptake in the pancreatic head. Seven of seven (100%) patients with neuroendocrine (NE) tumors had definite visual uptake. Uptake was 2.7× more likely benign than malignant. Using a three-dimensional region of interest (ROI) method, the pancreatic head-to-liver ratio was 0.91±0.38 (0.37–1.63) for benign uptake and 8.2±7.3 (1.79–23.6) for pathologic uptake ( P <0.001). A threshold of 1.67 provided 100% accuracy for determining the presence or absence of a pancreatic head NE tumor. Using a two-dimensional ROI method, the uptake ratio was 0.88±0.37 (0.28–1.73) for benign and 7.5±6.2 (1.85–19.6) for pathologic uptake ( P <0.001); a ratio threshold of 1.62 provided 97% accuracy. There was no difference between the uptake ratios at 4 and 24 h. Conclusion: 111 In pentetreotide uptake in the pancreatic head is common and more frequently benign than malignant. Using simple ROI ratiometric methods helps to differentiate benign physiologic from malignant NE tumor uptake.